2022
DOI: 10.1038/s41598-022-13302-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined model of topside ionosphere and plasmasphere derived from radio-occultation and Van Allen Probes data

Abstract: In the last years, electron density profile functions characterized by a linear dependence on the scale height showed good results when approximating the topside ionosphere. The performance above 800 km, however, is not yet well investigated. This study investigates the capability of the semi-Epstein functions to represent electron density profiles from the peak height up to 20,000 km. Electron density observations recorded by the Van Allen Probes were used to resolve the scale height dependence in the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
8
1
1
Order By: Relevance
“…Furthermore, it is possible to connect the model presented here to the plasmaspheric altitudes. Recently, Prol et al 33 demonstrated that the scale height in the plasmasphere exhibits a quadratic dependence on altitude, and found a functional dependence which allowed to connect the radio occultation profiles with in situ observations of electron density in the plasmasphere made by the Van Allen Probes mission. Using the methodology of Prol et al 33 , it is possible to connect the model presented in this study to the plasmasphere, making it a full topside option valid up to the GNSS altitudes and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is possible to connect the model presented here to the plasmaspheric altitudes. Recently, Prol et al 33 demonstrated that the scale height in the plasmasphere exhibits a quadratic dependence on altitude, and found a functional dependence which allowed to connect the radio occultation profiles with in situ observations of electron density in the plasmasphere made by the Van Allen Probes mission. Using the methodology of Prol et al 33 , it is possible to connect the model presented in this study to the plasmasphere, making it a full topside option valid up to the GNSS altitudes and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Prol et al 33 demonstrated that the scale height in the plasmasphere exhibits a quadratic dependence on altitude, and found a functional dependence which allowed to connect the radio occultation profiles with in situ observations of electron density in the plasmasphere made by the Van Allen Probes mission. Using the methodology of Prol et al 33 , it is possible to connect the model presented in this study to the plasmasphere, making it a full topside option valid up to the GNSS altitudes and beyond. Therefore, the model developed in this study combined with its plasmaspheric extension can be incorporated into the IRI as a novel option for specifying the topside ionosphere and plasmasphere.…”
Section: Discussionmentioning
confidence: 99%
“…They can be efficiently used to represent the ionospheric delay in the signal path between the classic GNSS satellites and the ground. However, in LEO-PNT, a large region above the LEO orbit height (up to 20,000 km), corresponding to the topside ionosphere and plasmasphere [82], [83], [84], should be removed from the current ionospheric models. In this regard, three-dimensional (3D) models are more realistic for LEO-PNT systems.…”
Section: Ionospherementioning
confidence: 99%
“…Existe uma vasta gama de investigações que ainda se faz necessária nessa área de pesquisa, não apenas em relação às novas missões, mas também quanto às configurações de processamento, metodologias envolvidas na obtenção e validação dos perfis atmosféricos e, ainda, as metodologias de assimilação dos dados de RO-GNSS em modelos atmosféricos. Diversos estudos recentes apresentam importantes contribuições em relação à atmosfera neutra (ANTHES et al, 2022;FU et al, 2022;YANG, 2022) e à ionosfera (BERGSSON;SYNDERGAARD, 2022;SUN et al, 2022;PROL et al, 2022).…”
Section: Considerações Finaisunclassified